Describing Agent-Oriented Design Patterns in Tropos - Silva, Carla; Castro, Jaelson; Tedesco, Patrícia; Silva, Ismênia (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2005: Anais do XIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2005.23808, 2005)
The increasing interest in software agents and multi-agent systems has recently led to the development of new methodologies based on agent concepts. The Tropos framework offers an approach to guide the development of agent-oriented systems by using concepts based on requirements engineering. In this paper, we concentrate on the detailed design and implementation phases of the Tropos approach. In particular, we outline a method for choosing and applying agent-oriented design patterns. Moreover, we discuss how agent-oriented design patterns could be properly described, and provide some means of implementing them in a particular agent environment JADE. The proposed pattern description includes a template as well as three UML extended diagrams to capture the behaviour, structure and collaboration of each pattern. By doing so, we hope to improve the understanding and usage of agent-oriented design patterns. We apply the proposal to an e-News example.